Optical alignment and radiative flux characterization of a multi-source high-flux solar simulator. (1st April 2022) - Pottas, Johannes; Li, Lifeng; Habib, Mustafa; Wang, Chi-Hwa; Coventry, Joe; Lipiński, Wojciech
Abstract: High-flux solar simulators are research-grade sources of artificial radiation mimicking optical characteristics of concentrating solar systems. They allow for experimental evaluation of high-temperature solar thermal devices and materials under controlled and reproducible conditions. In this study, we demonstrate the application of close-range photogrammetry in tandem with radiometry to optically align radiation modules of a multi-source high-flux solar simulator and to characterize its radiative output. The photogrammetric setup consists of photogrammetry targets, a digital camera and photogrammetry software. The radiometric measurements are conducted using mobile Lambertian targets, a heat flux gauge, and a complementary metal-oxide semi-conductor camera equipped with neutral density filters. An iterative procedure for adjusting lamp positions allows obtaining optical configurations of radiative modules meeting experimental requirements of high and ultra-high temperature solar thermal and thermochemical research. Close-range photogrammetry is demonstrated to be a convenient and effective method to obtain the as-built geometric configuration of the solar simulator setup. We report characteristics of an example radiative module configuration for a subset of six radiation modules. The peak and mean radiative fluxes over a 60-mm diameter flat target located in the focal plane are 3080 kW m −2 and 1135 kW m −2, respectively. The mean aiming error, defined as the average distance between theoretical and actual aiming points in the focal plane, is reduced from 37.20 mm to 4.50 mm for the pre- and post-alignment configurations, respectively. Highlights: Optical alignment and radiative flux characterization of a high-flux solar simulator are presented. A combined methodology of close-range photogrammetry and radiometry is applied. Close-range photogrammetry allows capturing the geometric configuration of the entire HFSS setup. The mean aiming error is reduced from 37.20 mm to 4.50 mm after photogrammetry alignment. A mean radiative flux of 1135 kW m -2 is obtained over a 60-mm dia. flat target using six lamps.